Analisis Pemisahan Gelombang Geser di Bawah Daerah Busur Vulkanik Sumatra yang Diperoleh dari Stasiun Jaringan Seismik Broadband. - Lewi Ristiyono; Chichi Nurfaizah; Suhenri Purba; Marhaposan Situmorang (Journal of Computation Physics and Earth Science (JoCPES), 2021)
The observation of broadband network seismic had been deployed in Sumatra For-Arc. The waveform data for this study were recorded from January 2014 – December 2016. The earthquake event data were selected with the epicenter of around 950 – 1800 in distance and Magnitude with more than 7 Mw. In this case, we use shear wave splitting to determine an anisotropic structure in Sumatra For-arc. Seismic Anisotropy can perform as a tool to classify and observe anisotropic structures of subsurface deformation processes beneath Sumatra For-Arc. The valid outcomes, in this case, have been gained that they only correspond to the upper layer, which has the delay time duration of 0.5 – 0.8 s is the anisotropic layer located in the Mentawai Island. The fast an anisotropic polarization direction found in Sumatra For-arc are parted into NE-SW direction found on the upper layer.